Antistaphylococcal activity of 3D-printed titanium implants with magnesium‑containing multicomponent coating - Ekaterina M. Gordina; Svetlana A. Bozhkova; Dmitry V. Labutin; Marina V. Bogma; Alexander A. Eruzin (Гений oртопедии)
Introduction Titanium has been successfully employed as artificial implants in orthopedic surgery for decades. Surgical intervention, specifically the implantation of medical devices, carries a risk of implant-associated infection (IAI), the causative agents of which are staphylococci in more than half of the cases. The objective was to evaluate the antibacterial, antibiofilm activity and cytocompatibility of a multicomponent coating with magnesium and silver oxides on the surface of 3D titanium samples. Material and methods The MgO-AgO-MgO complex The MgO-AgO-MgO complex was applied to 3D samples of medical titanium. Elemental analysis was performed using a TM 4000 Plus scanning electron microscope. The samples were incubated with bacteria for 24 hours to identify antibacterial activity against S. aureus. S. aureus biofilms were formed by immersing the test samples in a nutrient medium with bacteria. After a 24‑hour incubation, the samples were washed, placed in an ultrasonic washer, and then sonication fluid was seeded using the sector seeding method. The cytocompatibility of the coating was assessed on a culture of eukaryotic cells of the Vero line. Results Elemental analysis and mapping confirmed the uniform distribution of oxides on the surface of 3D titanium samples. The coating was characterized by antibacterial activity against S. aureus for three days. The MgO-AgO-MgO complex effectively prevented S. aureus adhesion and microbial film formation, while the control samples showed biofilm formation by staphylococci. However, cytocompatibility analysis of the 3D samples showed no viable cells after 72 h of incubation in a medium with an extract from coated titanium samples. Discussion Despite a decrease in antibacterial properties on day 4, the MgO-AgO-MgO complex prevented microbial adhesion to the surface of the samples which ensured protection of the implant from the formation of microbial biofilm. The cytotoxicity of the complex was caused by significant activation of lipid peroxidation reactions, which resulted in suppression of the viability of eukaryotic cells. Conclusion The MgO-AgO-MgO coating prevents primary interaction between the pathogen and the abiotic surface, which is one of the main factors in preventing the development of IAI and the relapses after revision surgeries with implant replacement. However, the high level of cytotoxicity requires further modification of the coating application technique and its composition.